Cancer In John Green's The Fault In Our Stars Novel (2012): A Sociological Approach - Setyowati, Dewi; , Dr. Phil. Dewi Chandraningrum, M. Ed; , Titis Setyabudi, S.S., M. Hum (2016)
The major problem of this study is cancer. Someone who suddenly gets a cancer, they have to experience a big change in their life. The objective of this study is to analyze this novel based on the Sociological Approach. The Writer employs qualitative method. The writer uses two data sources: primary and secondary. The primary data source of the study is The Fault in Our Stars novel by John Green. The secondary data of the study are taken from any information related to the novel. The method of data collection is the descriptive qualitative research. Based on the analysis, the researcher gets some conclusions. The study shows that the problem faced by the major and minor characters about cancer. It is proven by their life that they have been dealing with cancer. But, cancer doesn't block them to reach their dream. They want to meet Peter Van Houten in Amsterdam, the author of An Imperial Affliction. The Hazel and Augustus's favourite novel.